The adjustment of the us strategy towards Asean in recent years and the response of the Mekong sub-region countries - Van, Tran Thi Thanh (Edelweiss Applied Science and Technology, 2024)
The article analyzes the strategic changes of the US in Southeast Asia in recent years in the context of increasingly fierce competition between major powers and many hot spots of disputes in the region that have not shown signs of cooling down. The US’s interest in and actions towards Southeast Asia has been adjusted towards greater engagement, not only with the traditional region (island Southeast Asia) but also the Mekong Sub-region, to prevent China’s growing influence. The US’s strategic adjustments have had certain positive and negative impacts on the Mekong Sub-region countries in planning and implementing their foreign policies, aiming to create a balance of influence between major powers. To optimize advantages, in the coming time, the Mekong Sub-region countries need to strengthen regional connectivity, and interweave the interests of major powers to promote cooperation but also avoid being caught up in the vortex of great power competition in the region.